2022
DOI: 10.1002/jcu.23308
|View full text |Cite
|
Sign up to set email alerts
|

Fetal brain biometry and cortical development in congenital heart disease: A prospective cross sectional study

Abstract: Objective To evaluate brain biometry and cortical development by neurosonography in fetuses with congenital heart defect (CHD) and evaluate differences among different type of CHD. Methods In a prospective cross sectional study singleton fetus with CHD were matched with controls and grouped into two categories according to the predicted severity of cerebral arterial oxygen deficit induced by the CHD: Group A mildly reduced or normal and Group B moderately to severely reduced. Neurosonography was done at 30–33 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“… 14 , 15 Cortical evaluation was performed following a methodology previously developed. 16 Insula depth was obtained from the trans‐thalamic axial plane tracing a vertical line perpendicular to the midline starting from the distal portion of the cavum septum pellucidum to the proximal border of the cortex. To evaluate the Sylvian fissure (SF) the same line was continued from the border of the insula to the internal border of the parietal bone.…”
Section: Methodsmentioning
confidence: 99%
“… 14 , 15 Cortical evaluation was performed following a methodology previously developed. 16 Insula depth was obtained from the trans‐thalamic axial plane tracing a vertical line perpendicular to the midline starting from the distal portion of the cavum septum pellucidum to the proximal border of the cortex. To evaluate the Sylvian fissure (SF) the same line was continued from the border of the insula to the internal border of the parietal bone.…”
Section: Methodsmentioning
confidence: 99%
“…The potential advantage of this procedure is to prevent the damage of the left ventricle and the progression to hypoplastic left heart syndrome. Further it may be speculated that an early replacement of a near normal perfusion of the ascending aorta may reduce the neurological impairment frequently associated with this obstructive congenital heart diseases 4 …”
Section: Figurementioning
confidence: 99%
“…Further it may be speculated that an early replacement of a near normal perfusion of the ascending aorta may reduce the neurological impairment frequently associated with this obstructive congenital heart diseases. 4 However, the potential benefit of FAV must be weighed against the known risk of fetal demise and the possibilities of a technically unsuccessful procedure or postnatal single ventricle (SV) circulation despite a technically successful FAV. The analysis of data reported by International Fetal Cardiac Intervention Registry about fetuses who underwent FAV from 2002 to 2018, showed that this procedure may be successful but it is an high-risk procedure.…”
mentioning
confidence: 99%
“…During neurosonographic evaluation, measurements related to the corpus callosum (CC), subarachnoid space, insula, and parieto-occipital fissure depths in the axial image are primarily used in neurosonographic research. [9][10][11][12] However, further studies are needed to comprehensively assess the fetal intracranial structures and spaces with additional planes to increase the reliability of the correlation between the detected measurement differences and structural defects, especially in women with DM, which has a remarkable potential to cause fetal brain abnormalities. 8,13 To date, no published study has undertaken an assessment of brain structures in women with DM at gestational ages beyond 20 weeks, with particular emphasis on simultaneous measurements of CC width and depth in the midsagittal image; and lateral craniocortical (LCC) and posterior craniocortical (PCC) widths of the subarachnoid space and insular and parieto-occipital fissure depths in the axial image.…”
Section: Introductionmentioning
confidence: 99%
“…The various intracranial structures and spaces, which technical advances in neurosonography have made it possible to measure, are increasingly being taken into account in the study of disorders of brain development during fetal life. During neurosonographic evaluation, measurements related to the corpus callosum (CC), subarachnoid space, insula, and parieto‐occipital fissure depths in the axial image are primarily used in neurosonographic research 9–12 . However, further studies are needed to comprehensively assess the fetal intracranial structures and spaces with additional planes to increase the reliability of the correlation between the detected measurement differences and structural defects, especially in women with DM, which has a remarkable potential to cause fetal brain abnormalities 8,13 .…”
Section: Introductionmentioning
confidence: 99%